SBIR Program Diversity and Assessment Challenges: Report of a Symposium - National Research Council (The National Academies Press, 2004)
In response to a Congressional mandate, the National Research Council conducted a review of the Small Business Innovation Research Program (SBIR) at the five federal agencies with SBIR programs with budgets in excess of $100 million (DOD, NIH, NASA, DOE, and NSF). The project was designed to answer questions of program operation and effectiveness, including the quality of the research projects being conducted under the SBIR program, the commercialization of the research, and the program's contribution to accomplishing agency missions. The first in a series to be published in response to the Congressional request, this report summarizes the presentations at a symposium convened at the beginning of the project. The report provides a comprehensive overview of the SBIR program's operations at the five agencies responsible for 96 percent of the program's operations.
Keywords: Industry and Labor